(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This scientific report deals with the quality of groundwater for drinking purpose in the hard-rock aquifer of Dharmapuri district, Tamil Nadu South India. 135 Groundwater samples were collected based on the equal grid method and groundwater quality was assessed. Geographically the aerial extent of the study area is plain portion 3313.15 Sq.Km and Hill and forest 1346.25 Sq.Km. groundwater samples was analyzed in various physicochemical parameters and major ion chemistry like pH, EC, TDS, Ca2+, Mg2+, Na+, K+, HCO3-, Cl-, SO42-, NO3- and F-. Based on the analytical results, to prepared spatial distribution maps with help of WHO standard. ArcGIS was employed. Attributes were linked and spatial interpolation tool was used. IDW technique was followed for raster and vector mapping. Finally integration analysis was carried out to locate the worst quality zone. Based on the analysis, most of the samples are suitable for drinking. The final integrated map (Drinking quality) reveals that for suitable for drinking and domestic purpose. â€œNot permissibleâ€ water quality zone cover about area 2467.09 sq. km respectively. While â€œMaximum allowableâ€ water quality zone cover an area of 836.87 sq. km. The â€œMost desirableâ€ water quality zone an area 9.19 sq.km for drinking and domestic purposes.